(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The strength of bonding between protective-decorative coatings and the surface of wood materials, plays a major role in the durability of the wooden products, exposed to atmospheric conditions in the open area. This article analyzes the effects, that has the protective-decorative coatings, like durability of the natural oils and synthetic lacquer products used for protective layer of wood and the surface condition, after stay under the environmental impacts. To achieve this aim, an experimental stand was built according to standard EN 350:2016 and mounted in the territory of Yundola, Velingrad municipality. By the determined 12 months under review time period it is followed the change of surface of different types of natural oils and synthetic lacquer products used for protection of wood exposed to open area. The change in color is reflected, the damage to the surface of the used protective-decorative coatings, the mold formation, and the moisture resistance of the protective coatings. The results are analyzed and graphically presented.